Transcriptome Profiling of Acquired Gefitinib Resistant Lung Cancer Cells Reveals Dramatically Changed Transcription Programs and New Treatment Targets - Wei, Nan; Song, Yong'an; Zhang, Fan; Sun, Zhifu; Zhang, Xiaoju (Frontiers in Oncology, 2020)
Background. Targeted therapy for lung cancer with epidermal growth factor receptor (EGFR) mutations with tyrosine kinase inhibitors (TKIs) represents one of the major breakthroughs in lung cancer management. However, gradually developed resistance to these drugs prevents sustained clinical benefits and calls for resistant mechanism research and identification of new therapeutic targets. Acquired T790M mutation accounts for majority of resistance cases yet transcriptome changes in these cells are less characterized and it is not known if new treatment targets exist by available drugs. Methods. Transcriptome profiling was performed for lung cancer cell line PC9 and its resistant line PC9GR after long-term exposure to gefitinib through RNA sequencing. Differentially expressed genes and changed pathways were identified along with existing drugs targeting these up-regulated genes. Using 144 lung cancer cell lines with both gene expression and drug response data from cancer cell line encyclopedia (CCLE) and Cancer Therapeutics Response Portal (CTRP), we screened 549 drugs whose response was correlated with these up-regulated genes in PC9GR cells and top drugs were evaluated for their response in both PC9 and PC9GR cells. Results. In addition to the acquired T790M mutation, the resistant PC9GR cells had very different transcription programs from the sensitive PC9 cells. Multiple pathways were changed with the top ones including TNFA signaling, Androgen/Estrogen response, P53 pathway, MTORC1 Signalling, Hypoxia and Epithelial Mesenchymal Transition. Thirty-two up-regulated genes had available drugs that can potentially be effective in treating the resistant cells. From response profiles of CCLE, we found 17 drugs whose responses were associated with at least 4 of these up-regulated genes. Among 4 drugs evaluated (dasatinib, KPT-185, trametinib and pluripotin), all except trametinib demonstrated strong inhibitory effects on the resistant PC9GR cells among which KPT185 was the most potent.KPT-185 suppressed growth, caused apoptosis, and inhibited migration of the PC9GR cells at the similar (or better) rates as the sensitive PC9 cells in a dose-dependent manner. Conclusions. Acquired TKI resistant lung cancer cells (PC9GR) have dramatically changed transcription and pathway regulation which expose to new treatment targets. Existing drugs may be repurposed to treat those patients with developed resistance to TKIs.